Reconstruction of frontal bone with custom-made prosthesis using rapid prototyping - Florentino, Vincius Gabriel Barros; De Mendonça, Diego Santiago; Bezerra, Ariel Valente; De Freitas Silva, Leonardo [UNESP]; Pontes, Rafael Figueiredo; De Melo, Carlos Vincius Mota; Rodrigues Mello, Manoel De Jesus; De Aguiar, Andrea Silvia Walter (Wolters Kluwer, 2016)
Frontal bone fracture treatment is still an issue of research in craniofacial surgery and neurosurgery. The aims of the treatment are to reduce the complication risks and to keep the aesthetic of the face. Before the management of this fracture type, it is necessary to consider the permanence or not of the frontal sinus function. Rapid prototyping has been an aid tool on planning and simulation of the surgical procedure, improving the diagnostic quality and the implant manufacture, beyond reducing the operative time. Among the used materials on treatment of these fractures, titanium mesh shows large versatility and ease of handling. Poly(-methyl methacrylate) has been used in defects of partial thickness or irregularities on cranial surface. The aim of this study is to report a case of a patient presenting sequelae of large fracture of anterior wall of frontal bone, treated by a titanium mesh associated with the customized poly(methyl methacrylate) implant from the rapid prototyping. It could be concluded that the use of this technique showed itself effective on patient treatment, and rapid prototyping demonstrated being a valuable tool showing predictable and satisfactory results.
Keywords: Craniocerebral trauma; Polymethyl methacrylate; Surgical mesh